Immunohistochemical approach to obesity disease in terms of expression levels of glutathione s-transferase (sigma, zeta, theta) isozymes - Davudov, Mahammad; Buluş, Hakan; Dirican, Onur; Kaygın, Pınar; Güler Şimşek, Gülçin; Yılmaz Sarıaltın, Sezen; Gürbüz, Fatıma Nurdan; Oğuztüzün, Serpil (The European Research Journal, 2023)
Objectives: Obesity is a complex multifactorial disease with recently increasing prevalence and incidence. Several studies have been conducted to explain the ethiology, pathophysiology, epidemiology, molecular and genetic mechanisms, and effective treatments of obesity. Glutathione S-transferase (GST) S1, GSTZ1, and GSTT1 are essential enzymes for oxidative stress and metabolism-related disorders. For this purpose, we aimed to reveal the role of GSTS1, GSTZ1, and GSTT1 in obesity. Methods: The gastric tissue samples were taken from the patients diagnosed with obesity who underwent bariatric surgery in Ankara Keçiören Training and Research Hospital General Surgery Clinic between 2017 and 2019. Immunostaining was performed on paraffin-embedded tissues to evaluate GSTS1, GSTZ1, and GSTT1 expressions. Laboratory data of the patients were recorded. All the results were analyzed statistically. Results: Weak GSTS1 expression was observed in 38.1% of tissues and moderate in 6.3%. 37.3% of the tissues presented weak GSTZ1 expression, and 11 (8.7%) displayed moderate. There were weak GSTT1 expressions in 7.1% of the tissues and moderate 0.8% of them. A positive and statistically significant correlation was observed between GSTS1 and GSTT1 expression levels ((r)=0.028, p = 0.010; p < 0.05). There were no significant differences between expression levels and gender, age, comorbidities, and medication usage (p > 0.05). Conclusions: GSTs, in particular GSTS1, GSTT1, and GSTZ1, might contribute to molecular mechanisms and the progression of obesity. In our study, GSTS1, GSTT1, and GSTZ1 were found to be moderately expressed in gastric tissues taken from obese patients. However, new studies using more samples and advanced techniques are needed to elucidate the relationship.